Science's need for Philosophy and Strengthening the Links between them (The International Journal for Scientific Research, 2024)
There is no doubt that our age is the age of science in the full meaning of the word in terms of knowledge, methodology and technology. This is evident through what we are witnessing of a huge scientific explosion. A drop of water, which was a simple compound, became a world full of secrets. Scholars of all disciplines research it. It is no longer a simple substance as we imagined it before but is a compound of hydrogen and oxygen in an accurate proportion. Biologists say that it is a completely natural museum of primitive life forms, including bacteria, microbes, fungi and parasites. As for the ecologists, they assert that a drop of water is a true mirror of all what pollutes the environment.Yet, this scientific development is not a rootless fruit. Rather, its origins go back to three centuries ago. Man in it searched and strived to understand nature and comprehend it using the reason. Philosophy was drawing attention to the first issues that occupied and still preoccupy scientists today. It preceded science until the latter reached what it has reached today.Whatever the importance of the transformations that occurred in the sciences and their development, philosophy has been playing a role in it. It is the first target of the mind.Philosophy in every era and at every moment opens our thinking to new issues that keep pace with that era. Indeed, philosophical questioning does not cease, even if it is marginalized in its moment, or in its era. It would certainly be in the service of all sciences and presented. Hence, we must strengthen the role of philosophy in light of the current transformations.
Keywords: Philosophy; Science; Epistemology; Logic; Curriculum